Value of Magnetic Resonance Imaging for Diagnosis of Dentigerous Cyst - Pinto, Antonione Santos Bezerra; Costa, Andrï¿½ Luiz Ferreira; Galvï¿½o, Neiandro Dos Santos; Ferreira, Thï¿½sia Luiz Dias; Lopes, Sï¿½rgio Lï¿½cio Pereira De Castro [UNESP] (Hindawi, 2016)
Odontogenic cysts have a high prevalence in the dental clinic population, with dentigerous cyst being one of the most frequent ones and whose aetiology involves accumulation of fluid between the reduced enamel epithelium and the crown of an unerupted tooth. In the diagnostic process of these lesions, one should consider complementary imaging exams such as conventional radiography and computed tomography, which are commonly used for providing anatomical information on the tissues compromised by the lesion, but not on the nature of it. Magnetic resonance imaging (MRI) scans are noninvasive modalities which, due to their unique acquisition characteristics, can provide distinct information on the nature of the lesion. This study reports on a case of dentigerous cyst in the mandible of a 9-year-old patient, documented by means of different imaging modalities. MRI played an important role in both diagnosis of the lesion and differential diagnosis between neoplastic lesions presenting similar imagenological behaviour under other techniques of radiography.